Abrogation of airway hyperresponsiveness but not inflammation by rho kinase insufficiency. Issue 2 (February 2015) - Kasahara, David I.; Ninin, Fernanda M. C.; Wurmbrand, Alison P.; Liao, James K.; Shore, Stephanie A.
Summary Background Major features of allergic asthma include airway hyperresponsiveness (AHR), eosinophilic inflammation, and goblet cell metaplasia. Rho kinase (ROCK) is a serine/threonine protein kinase that regulates the actin cytoskeleton. By doing so, it can modulate airway smooth muscle cell contraction and leucocyte migration and proliferation. This study was designed to determine the contributions of the two ROCK isoforms, ROCK1 and ROCK2, to AHR, inflammation and goblet cell metaplasia in a mast cell‐dependent model of allergic airways disease. Methods and Results Repeated intranasal challenges with OVA caused AHR, eosinophilic inflammation, and goblet cell hyperplasia in wild‐type (WT) mice. OVA‐induced AHR was partially or completely abrogated in mice haploinsufficient for ROCK2 (ROCK2+/‐) or ROCK1 (ROCK1+/−), respectively. In contrast, there was no effect of ROCK insufficiency on allergic airways inflammation, although both ROCK1 and ROCK2 insufficiency attenuated mast cell degranulation. Goblet cell hyperplasia, as indicated by PAS staining, was not different in ROCK1+/− vs. WT mice. However, in ROCK2+/− mice, goblet cell hyperplasia was reduced in medium but not large airways. Maximal acetylcholine‐induced force generation was reduced in tracheal rings from ROCK1+/− and ROCK2+/− vs. WT mice. The ROCK inhibitor, fasudil, also reduced airway responsiveness in OVA‐challenged mice, without affecting inflammatory responses. Conclusion In a mast cell model of allergic airways disease, ROCK1 and ROCK2 both contribute to AHR, likely through direct effects on smooth muscle cell and effects on mast cell degranulation. In addition, ROCK2 but not ROCK1 plays a role in allergen‐induced goblet cell hyperplasia.